Negative electrode lithium supplement agent, preparation method and application of negative electrode lithium supplement agent in lithium ion battery
By using a metal organic framework to encapsulate lithium nanoparticles in lithium batteries, the lithium loss and safety problems during the charging and discharge process of lithium batteries are solved, and higher safety performance, conductivity and stability are achieved.
Patent Information
- Application Number
- CN202411693402.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
AI Technical Summary
During the first charging and discharging process of existing lithium batteries, the electrolyte forms a solid electrolyte interface film on the surface of the graphite negative electrode, resulting in irreversible loss of lithium, reducing battery capacity and energy density, and the high reactivity of metal lithium powder brings safety problems.
Metal organic frameworks (MOFs) are used as precursor materials, and lithium and MOF are encapsulated in situ in a thin carbon film through an annealing step to form a composite material of lithium nanoparticles and conductive carbon matrix as a negative electrode lithium supplement agent.
It improves the safety performance, conductivity and stability of lithium batteries, effectively prevents safety problems caused by the high activity of lithium powder, and improves the energy density and cycle life of the battery cell.
Smart Images

Figure BDA0005151550750000051 
Figure HDA0005151550760000011
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium batteries, and in particular to a negative electrode lithium supplement and a preparation method thereof, and application thereof in lithium ion batteries. Background Art
[0002] During the first charge and discharge process of lithium batteries, the electrolyte forms a solid electrolyte interface film (SE film) on the surface of the graphite negative electrode, which consumes a lot of lithium, resulting in the attenuation of battery capacity and energy density. In order to offset the irreversible lithium loss caused by the formation of the SEI film and improve the energy density and cycle life of lithium batteries, more and more researchers have developed lithium replenishment technology.
[0003] At present, in order to solve the above technical problems, the invention patent application with publication number CN 116207376 A proposes a lithium supplement agent and its preparation method and a lithium ion battery, wherein the lithium supplement agent includes a conductive polymer and lithium doped in the conductive polymer. The invention patent application with publication number CN 118117059 A proposes a composite negative electrode material including carbon nanotubes with a three-dimensional cross-linked network structure and lithium metal attached to the inner wall of the carbon nanotubes, which can be used as a negative electrode lithium supplement agent. In the prior art, in order to solve the technical problem of negative electrode lithium supplementation, the main method is to directly add lithium powder to the negative electrode material, but due to the high reactivity of metallic lithium powder, there are still major safety issues. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a negative electrode lithium supplement material and a preparation method thereof, which, as a negative electrode lithium supplement, has higher safety performance, conductivity and stability, and can effectively prevent the safety problems caused by the high activity of lithium powder.
[0005] In one aspect of the present invention, the present invention proposes a negative electrode lithium supplement. According to an embodiment of the present invention, the negative electrode lithium supplement includes a metal organic framework, lithium nanoparticles and a thin carbon film, and the metal organic framework and lithium nanoparticles are in situ encapsulated in the thin carbon film. The present invention uses a metal organic framework (MOFs) as a precursor / template material, and the metal organic framework is a new type of crystalline porous material that self-assembles transition metal ions and organic ligands to form a periodic network structure. MOFs have the characteristics of high porosity, low density, regular pores, and adjustable pore size. Using MOFs as a precursor, the present invention encapsulates lithium and MOF in situ in a thin carbon film (Li@CF) through a simple annealing step. The combination of lithium nanoparticles and a conductive carbon matrix can not only reduce the unsafety of highly active lithium, but also effectively improve the energy density, conductivity and long-term stability of the battery cell. The negative electrode lithium supplement has higher safety performance, conductivity and stability, and can effectively prevent safety problems caused by the high activity of lithium powder.
[0006] In another aspect of the present invention, the present invention provides a method for preparing a negative electrode lithium supplement. According to an embodiment of the present invention, the method comprises:
[0007] S1: LiNO3 and 1,3,5-benzenetricarboxylic acid are mixed to obtain Li-MOF;
[0008] S2: annealing the Li-MOF to obtain a negative electrode lithium supplement.
[0009] The method is simple to operate, and the negative electrode lithium supplement material prepared according to the method has higher safety performance, conductivity and stability as a negative electrode lithium supplement, and can effectively prevent safety problems caused by high activity of lithium powder. Among them, metal organic frameworks (MOFs) are a new type of crystalline porous material with a periodic network structure formed by self-assembly of transition metal ions and organic ligands. MOFs have the characteristics of high porosity, low density, regular pores, and adjustable pore size, and have obvious advantages in high-performance materials. The carbon film prepared by MOF precursor can effectively improve the conductivity and ion transfer rate of the material, greatly improving the performance of lithium-ion batteries. At the same time, carbon coating also provides a guarantee for the safety of use.
[0010] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:
[0011] According to an embodiment of the present invention, the mass ratio of the LiNO3 to the 1,3,5-benzenetricarboxylic acid is (1-20):1.
[0012] According to an embodiment of the present invention, the mass ratio of the LiNO3 to the 1,3,5-benzenetricarboxylic acid is (2.5-15):1.
[0013] According to an embodiment of the present invention, the mixing treatment is performed by first dissolving LiNO3 and 1,3,5-benzenetricarboxylic acid in methanol to obtain a mixed solution, and then heating and post-treating the mixed solution.
[0014] According to an embodiment of the present invention, the mass ratio of the 1,3,5-benzenetricarboxylic acid to the volume ratio of the methanol is (10-15):1.
[0015] According to an embodiment of the present invention, the mass ratio of the 1,3,5-benzenetricarboxylic acid to the volume ratio of the methanol is 12.5:1.
[0016] According to an embodiment of the present invention, the temperature of the heating treatment is 120°C.
[0017] According to an embodiment of the present invention, the heating treatment time is 24 hours.
[0018] According to an embodiment of the present invention, the heating treatment is performed in a Teflon autoclave.
[0019] According to an embodiment of the present invention, the post-treatment includes cooling treatment, centrifugal treatment, washing treatment and drying treatment.
[0020] According to an embodiment of the present invention, the temperature of the cooling process is room temperature.
[0021] According to an embodiment of the present invention, the washing liquid in the washing treatment is methanol.
[0022] According to an embodiment of the present invention, the temperature of the drying process is 60°C.
[0023] According to an embodiment of the present invention, the drying process is performed in a vacuum environment.
[0024] According to an embodiment of the present invention, the temperature of the annealing treatment is 500°C.
[0025] According to an embodiment of the present invention, the annealing process is performed in an argon atmosphere.
[0026] According to an embodiment of the present invention, the annealing treatment time is 3 hours.
[0027] According to an embodiment of the present invention, the heating rate of the annealing treatment is 2° C. / min.
[0028] In another aspect of the present invention, the present invention further provides a negative electrode lithium supplement agent. According to an embodiment of the present invention, the negative electrode lithium supplement agent is prepared according to the method described above.
[0029] In another aspect of the present invention, the present invention further provides a negative electrode material for a lithium battery. According to an embodiment of the present invention, the negative electrode material for a lithium battery includes the negative electrode lithium supplement agent described above.
[0030] In another aspect of the present invention, the present invention further provides a lithium battery. According to an embodiment of the present invention, the lithium battery comprises the above-mentioned lithium battery negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0032] Figure 1 It is a preparation flow chart provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0033] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0034] Embodiment 1
[0035] 150 mg of LiNO3 and 750 mg of 1,3,5-benzenetricarboxylic acid (H3BTC) were dissolved in 60 ml of methanol.
[0036] The mixed solution was transferred into a Teflon autoclave and heated at 120°C for 24 h. After cooling to room temperature, the product was collected by centrifugation, washed with methanol several times, and dried under vacuum at 60°C overnight.
[0037] The obtained Li-MOF was directly annealed at 500°C in an argon atmosphere for 3 h with a heating rate of 2°C / min to finally obtain a Li@CF composite material.
[0038] The obtained Li@CF composite material, binder polyvinylidene fluoride (PVDF), and conductive agent conductive carbon were mixed in a mass ratio of 96:2:1 to obtain a negative electrode material mixture, and then 50% of the total weight of the negative electrode material mixture was added and mixed to obtain a negative electrode slurry. The negative electrode slurry was coated on both surfaces of the copper foil, dried at room temperature, transferred to an 80°C oven for 10 hours, and then rolled, slit, and sliced to obtain a negative electrode sheet.
[0039] The positive electrode material lithium iron phosphate, the binder polyvinylidene fluoride (PVDF), SP (super P), and the carbon nanotube (CNT) are mixed in a mass ratio of 96.2:1.8:1.5:0.5 to obtain a positive electrode material mixture, and then 65% of the solvent N-methylpyrrolidone (NMP) equivalent to the total weight of the positive electrode material mixture is added and mixed and stirred to obtain a positive electrode slurry; the positive electrode slurry is coated on both surfaces of the aluminum foil, and after drying at room temperature, it is transferred to an 80°C oven for drying for 10 hours, and then rolled, slit, and sliced to obtain a positive electrode sheet.
[0040] The solvent of the electrolyte is EC / PC / EMC / DEC (mass ratio is 1:1:1:1); the additive is vinylene carbonate (VC), and the amount of the additive is 2% of the total weight of the electrolyte; the lithium salt is lithium difluorophosphate (LiPO2F2), and the concentration of the lithium salt in the electrolyte is 15wt%.
[0041] The positive electrode sheet, the separator (PP) and the negative electrode sheet are stacked and assembled to obtain a battery cell, which is placed in a casing, injected with electrolyte after drying, and then subjected to packaging, standing, formation, constant capacity and other processes to obtain a soft-pack battery.
[0042] Embodiment 2
[0043] The difference from Example 1 is that the amount of LiNO3 used is different.
[0044] 50 mg of LiNO3 and 750 mg of 1,3,5-benzenetricarboxylic acid (H3BTC) were dissolved in 60 ml of methanol.
[0045] The mixed solution was transferred into a Teflon autoclave and heated at 120°C for 24 h. After cooling to room temperature, the product was collected by centrifugation, washed with methanol several times, and dried under vacuum at 60°C overnight.
[0046] The obtained Li-MOF was directly annealed at 500°C in an argon atmosphere for 3 h with a heating rate of 2°C / min to finally obtain a Li@CF composite material.
[0047] Embodiment 3
[0048] The difference from Example 1 is that the amount of LiNO3 used is different.
[0049] 300 mg of LiNO3 and 750 mg of 1,3,5-benzenetricarboxylic acid (H3BTC) were dissolved in 60 ml of methanol.
[0050] The mixed solution was transferred into a Teflon autoclave and heated at 120°C for 24 h. After cooling to room temperature, the product was collected by centrifugation, washed with methanol several times, and dried under vacuum at 60°C overnight.
[0051] The obtained Li-MOF was directly annealed at 500°C in an argon atmosphere for 3 h with a heating rate of 2°C / min to finally obtain a Li@CF composite material.
[0052] Comparative Example 1
[0053] The difference from Example 1 is that 1,3,5-benzenetricarboxylic acid (H3BTC) is not used.
[0054] 150 mg of LiNO3 was dissolved in 60 ml of methanol.
[0055] The mixed solution was transferred into a Teflon autoclave and heated at 120°C for 24 h. After cooling to room temperature, the product was collected by centrifugation, washed with methanol several times, and dried under vacuum at 60°C overnight.
[0056] The obtained Li-MOF was directly annealed at 500°C in an argon atmosphere for 3 h with a heating rate of 2°C / min to finally obtain a Li@CF composite material.
[0057] Comparative Example 2
[0058] The difference from the first embodiment is that LiNO3 is not used.
[0059] 750 mg of 1,3,5-benzenetricarboxylic acid (H3BTC) was dissolved in 60 ml of methanol.
[0060] The mixed solution was transferred into a Teflon autoclave and heated at 120°C for 24 h. After cooling to room temperature, the product was collected by centrifugation, washed with methanol several times, and dried under vacuum at 60°C overnight.
[0061] The obtained Li-MOF was directly annealed at 500°C in an argon atmosphere for 3 h with a heating rate of 2°C / min to finally obtain a Li@CF composite material.
[0062] Electrical performance test:
[0063] The batteries of the above-mentioned embodiments and comparative examples were subjected to cycle tests at 25±2°C with a voltage window of 2.5-3.65V and a current density of 1C / 1C.
[0064] Safety testing methods:
[0065] Puncture test: After charging the battery to 3.65V, use a 6mm steel needle to puncture at a speed of 5mm / s. The steel needle completely penetrates the entire large surface of the battery. Keep it for 60 minutes and observe whether there is fire, explosion, etc.
[0066] Overcharge experiment: After charging the battery to 3.65V, continue charging at 0.5C constant current until the voltage reaches 1.5 times the battery cell charging termination voltage or the charging time reaches 1h, then stop charging and observe for 60min to see if there is any fire or explosion.
[0067] The performance is shown in Table 1.
[0068] Table 1
[0069]
[0070] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0071] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A negative electrode lithium supplement, characterized in that: The negative electrode lithium supplement comprises a metal organic skeleton, lithium nanoparticles and a thin carbon film, and the metal organic skeleton and the lithium nanoparticles are in-situ encapsulated in the thin carbon film.
2. A method for preparing a negative electrode lithium supplement, characterized in that: include: S1: LiNO3 and 1,3,5-benzenetricarboxylic acid are mixed to obtain Li-MOF; S2: annealing the Li-MOF to obtain a negative electrode lithium supplement.
3. The method according to claim 2, characterized in that The mass ratio of the LiNO3 to the 1,3,5-benzenetricarboxylic acid is (1-20): 1; Optionally, the mass ratio of the LiNO3 to the 1,3,5-benzenetricarboxylic acid is (2.5-15):
1.
4. The method according to claim 2, characterized in that: The mixing treatment is performed by first dissolving LiNO3 and 1,3,5-benzenetricarboxylic acid in methanol to obtain a mixed solution, and then heating and post-treating the mixed solution; Optionally, the mass ratio of the 1,3,5-benzenetricarboxylic acid to the volume ratio of the methanol is (10-15):1; Optionally, the mass ratio of the 1,3,5-benzenetricarboxylic acid to the volume ratio of the methanol is 12.5:
1.
5. The method according to claim 4, characterized in that The temperature of the heating treatment is 120°C; Optionally, the heating treatment time is 24h; Optionally, the heat treatment is performed in a Teflon autoclave.
6. The method according to claim 4, characterized in that The post-treatment includes cooling treatment, centrifugal treatment, washing treatment and drying treatment; Optionally, the temperature of the cooling treatment is room temperature; Optionally, the washing liquid of the washing treatment is methanol; Optionally, the drying temperature is 60°C; Optionally, the drying process is carried out in a vacuum environment.
7. The method according to claim 2, characterized in that The annealing temperature is 500°C; Optionally, the annealing process is performed in an argon atmosphere; Optionally, the annealing time is 3h; Optionally, the heating rate of the annealing treatment is 2°C / min.
8. A negative electrode lithium supplement, characterized in that: The negative electrode lithium supplement is prepared by the method according to any one of claims 2-7.
9. A negative electrode material for a lithium battery, characterized in that: The negative electrode material of the lithium battery includes the negative electrode lithium supplement agent according to claim 1 or 8.
10. A lithium battery, characterized in that: The lithium battery comprises the lithium battery negative electrode material according to claim 9.
Citation Information
Patent Citations
Lithium supplement agent, preparation method thereof and lithium ion battery
CN116207376A
Composite negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
CN118117059A
Cited By
Composite MOF material, diaphragm, preparation method, battery and application
CN120473661A
Composite mof materials, separators, methods of preparation, batteries, and applications
CN120473661B